Effects of depth of field on eye movement. Issue 23 (31st October 2019) - Zhang, Tingting; Xia, Ling; Liu, Xiaofeng; Kong, Weijie; Wu, Xiaoli
Abstract : Depth of field is an important image feature, which can be used to enhance observers' perception of stereopsis. To explore how the depth of field influenced observers' attention in images, a within‐subject experiment including two factors, two scenes and six levels of depth of field, was performed. A remote desktop eye tracker, Tobii X120 was used to record participants' eye movement during the experiment. The results showed that the limited depth of field could direct observers' attention on the sharp area. However, manipulating depth of field in the same scene may not influence the distribution of observers' attention. In addition, it was concluded that depth from focus object influences observers' attention significantly, which means that the closer the object is, more attention the object obtains.